Manajemen Strategi Hubungan Masyarakat dalam Meningkatkan Minat Calon Siswa Bersekolah di Yayasan Surban MTs Pacet Mojokerto - Mika Julianti (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2021)
The main objective of carrying out a public relations strategy management in an educational institution is that the school continues to be in demand by educated participants and experiences development and progress from year to year. In conveying information, good communication is needed so that the information submitted can be received. In conveying information, public relations must have good strategic management and direction so that what is expected is carried out well. Data collection techniques are carried out by observation, interviews and documentation. The results of this study indicate that: (1) Public Relations Strategy Management in Increasing Student Interest in MTs Pacet Surban Foundation includes planning, communicating, implementing and evaluating well and directed by the school to attract the attention of prospective new students. (2) One of the inhibiting factors for public relations in increasing the interest of prospective students to attend the MTs Pacet Surban Foundation includes ineffective time in the implementation of management as well as long distances so that strategic management is not optimal.